Toxoplasmosis in goats - de Matos, Lucas Shigaki [UNESP]; Pierucci, Julia Cestari [UNESP]; da Silveira Neto, Luiz [UNESP]; Camossi, Lucilene Granuzzio [UNESP]; Cardia, Daniel Fontana Ferreira [UNESP]; da Costa, Alvimar José [UNESP]; dos Santos, Thais Rabelo; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2014)
Toxoplasma gondii is the etiologic agent of a worldwide distribution zoonosis. Cats are denominated as definitive hosts, but the infection affects many species including goats. Ingestion of oocysts excreted in definitive hosts feces, as well as water and soil, and via the transplacental represents the source of contamination. Goats infected with T. gondii will develop fever, anorexia, dyspnea, and pregnant females, in addition to those mentioned signs, will suffer miscarriage and stillbirth. Therefore this chapter will discuss relevant topics on the epidemiology, clinical signs, diagnosis, treatment and control of this disease so important and widespread in the world.